L’hématome spontané du muscle grand droit de l’abdomen chez le patient hémodialysé : une entité clinique rare.: Spontaneous hematoma of the right rectus abdominis muscle in a hemodialysis patient: a rare clinical entity - Zouaoui, Rihab; Sellami, Nada; Ben Ayed, Tasnim; Touileb, Hafedh; Ben Hmida, Fethi; Abderrahim, Ezzedine (African Journal of Nephrology, 2025)
Introduction: Hemodialysis patients are at risk of bleeding during dialysis sessions. Methods: We report a case of spontaneous hematoma of the right rectus abdominis muscle in a hemodialysis patient. Results: A 32-year-old man with Alport syndrome developed acute abdominal pain during hemodialysis session. Initial suspicion was acute appendicitis, but imaging revealed a hematoma in the right rectus abdominis muscle. The patient had a history of dry cough for two days. Symptomatic treatment was the adopted as the patient had a stable hemodynamic status. Conclusion: Spontaneous hematoma of the rectus abdominis muscle should be considered among the causes of acute abdominal pain in hemodialysis patients.